2009
DOI: 10.1016/j.jss.2008.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of DNA in Biologic Scaffold Materials

Abstract: Biological scaffold materials composed of extracellular matrix (ECM) are routinely used for a variety of clinical applications ranging from the treatment of chronic skin ulcers to hernia repair and orthopaedic soft tissue reconstruction. The tissues and species from which the ECM is harvested vary widely as do the methods used to remove the cellular component of the source tissues. The efficacy of decellularization procedures can be quantified by examination of the DNA that remains in the ECM. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
358
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(382 citation statements)
references
References 42 publications
14
358
0
10
Order By: Relevance
“…The DNA content was used as an indicator of the presence of residual cells in decellularized tissue [28]. The DNA from either native or decellularized tissue samples of known masses (approximately 20 mg) was isolated, purified and rehydrated per triplicate using the Wizard® Genomic DNA Purification Kit (Promega) according to the recommended protocol.…”
Section: Deoxyribonucleic Acid (Dna) Isolation and Quantificationmentioning
confidence: 99%
“…The DNA content was used as an indicator of the presence of residual cells in decellularized tissue [28]. The DNA from either native or decellularized tissue samples of known masses (approximately 20 mg) was isolated, purified and rehydrated per triplicate using the Wizard® Genomic DNA Purification Kit (Promega) according to the recommended protocol.…”
Section: Deoxyribonucleic Acid (Dna) Isolation and Quantificationmentioning
confidence: 99%
“…Several combination ECM materials isolated from mammalian sources are commercially available [52,77] , while others are in various stages of development and characterization [19,[78][79][80] .…”
Section: Polymersmentioning
confidence: 99%
“…In a randomized control trial of the Restore 1 patch, Iannotti et al [27] demonstrated no improvement in patients with Restore 1 augmentation when compared with patients who underwent the same procedure without xenograft addition. More recently, Restore 1 was found to contain a relatively high level of DNA within its matrix (1.13 ± 0.01 ng DNA/ mg dry weight) and has also resulted in an inflammatory result in 20% of patients whose rotator cuff tears were repaired with Restore 1 augmentation [22,38]. In a retrospective analysis, Walton et al [55] reported that patients whose rotator cuffs had been repaired with the Restore 1 patch experienced decreased post-repair strength, increased shoulder impingement, slower pain resolution after activity, and no decrease in retear rate when compared to patients whose rotator cuff tears had been repaired using standard surgical techniques.…”
Section: Ecm Augmentationmentioning
confidence: 99%
“…Zimmer 1 Collagen Repair Patch, marketed as Permacol 1 , (Tissue Science Laboratories PLC, Aldershot, Hampshire, UK), is a porcine dermal graft with no measurable DNA in its matrix and no reported inflammatory responses in patients [22]. One retrospective analysis of rotator cuff repair using Permacol 1 showed improved functional scores by 50% at 4.5 years postrepair [3].…”
Section: Ecm Augmentationmentioning
confidence: 99%
See 1 more Smart Citation